2009
DOI: 10.1093/hmg/ddn442
|View full text |Cite
|
Sign up to set email alerts
|

Functional SNPs in the SCGB3A2 promoter are associated with susceptibility to Graves' disease

Abstract: Graves' disease (GD) is one of the most common human autoimmune diseases, and recent data estimated a prevalence of clinical hyperthyroidism of 0.25-1.09% in the population. Several reports have linked GD to the region 5q12-q33; and a locus between markers D5s436 and D5s434 was specifically linked to GD susceptibility in the Chinese population. In the present study, association analysis was performed using a large number of single-nucleotide polymorphisms (SNPs) at this locus in 2811 patients with GD recruited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 38 publications
3
50
1
Order By: Relevance
“…In this study, we confirmed a role of the SCGB3A2 −112G>A polymorphism as a marker for GD susceptibility on chromosome 5q31-q33 that was previously shown by Song et al (2009) andSimmonds et al (2010). An association between the allele A and GD (OR=1.33, P=2.9×10 −5 ) observed in a Russian population was stronger than the size of effect of the carriage of this allele on susceptibility to GD in UK Caucasians (OR=1.18, P=0.007) (Simmonds et al 2010).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In this study, we confirmed a role of the SCGB3A2 −112G>A polymorphism as a marker for GD susceptibility on chromosome 5q31-q33 that was previously shown by Song et al (2009) andSimmonds et al (2010). An association between the allele A and GD (OR=1.33, P=2.9×10 −5 ) observed in a Russian population was stronger than the size of effect of the carriage of this allele on susceptibility to GD in UK Caucasians (OR=1.18, P=0.007) (Simmonds et al 2010).…”
Section: Discussionsupporting
confidence: 88%
“…Association between marker rs31480 of IL-3 and GD was not confirmed in a recent well-powered study of British Caucasians (Simmonds et al 2010). However, Simmonds et al (2010) replicated findings of Song et al (2009), who showed an association between GD and marker rs1368408 located in the promoter of the secretoglobin 3A2 (SCGB3A2) gene, in three independent Chinese population datasets. The human SCGB3A2 gene is assigned to chromosome 5q31-32 (Niimi et al 2001).…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Similarly, UGRP1 has been suggested to exhibit anti-inflammatory functions. It has been shown that UGRP1 is associated with an increased risk for Graves’ disease (17,18). However, there have been confounding results with regard to the correlation between UGRP1 gene polymorphisms and asthma risk (5,7,9,19).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing attention has previously been paid to the CT60 SNP of CTLA4 in patients with GD (26)(27)(28). However, the correlation between CT60 A/G and the development of GD varied among patients from different geographic populations (29). Thus, there are limited reports regarding an association between the CT60 SNP and GD in the Han population of Southern China.…”
Section: Introductionmentioning
confidence: 99%